Maszynerie afektywne Literackie strategie emancypacji w najnowszej polskiej poezji kobiet - Glosowitz, Monika (Nowa Humanistyka, 2019)
This book is the first monograph concerned with a feminist reading of Polish contemporary poetry to utilise tools of affective methodologies. It seeks to establish the extent to which affects contribute to the process of collective forms of existence. The book's main thesis assumes affects to be the triggers of action, particularly of critically modifying established narratives about emotive histories of societies which include the allotment of the capacity to feel in order to coercively classify the actors and actresses of collective life. Poetry, as a very particular instance of those various affective machineries, becomes yet another version of collective memory. Poetical representations, acting in synergy with transformations of the contemporary subject, operate on three levels: firstly, by reproducing normative images of womanhood in its relations with surroundings, secondly, by disturbing the said images through an, often critical, reformulating of them, or thirdly, by becoming postulated variants of those transformations. The semantic dominants one can find in recent women's poetry that, at the same time, constitute a portion of the broader symbolic feminine capital being a unified construct edifying the social discourses, pertain to the category of disease/illness, seeing, trauma and shame, the affective work, love, migration, and community.